Kompetensi Manajerial Kepala Sekolah dalam Meningkatan Kinerja Guru - Nasar, Ismail; Majir, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research intends to describe the role of principal managerial skills in improving teachers' performance at Wae Mbeleng SDK. The type used in this research was descriptive qualitative. The data source in this research was the principal, the teachers, and the essential documents of Wae Mbeleng SDK. The data collection technique used interviews, observation, and documentation. Data collection instruments used were interview guidelines which contained questionnaires related to the managerial skill of the principal and the teacher's performance. Data analysis in this research used the flow model of Miles and Huberman. The activity in data analysis that data reduction, data display, and conclusion/verification. The fallout of this research pointed out that: first, some of the teachers needed to prepare their RPP as teaching guidelines; hence, the learning flow required to be more precise, and the necessary learning goal to be attained. Second, the principal and the teachers knew the managerial skill which should have by the principal and the managerial skill which had inhered within the principal of Wae Mbeleng SDK. Third, the role of the principal's executive talent in the improvement of teacher performance at Wae Mbeleng SDK consisted of conceptual indicator skills, human relationship skills, and general skills grounded on the teacher's perception was the principal of Wae Mbeleng SDK had carried out his good managerial skill hence could give improvement to the teacher's performance. Dropped on the research fallout, the principal's administrative skill role could improve teachers' interpretation at Wae Mbeleng SDK.